(untitled) (Italian Journal of Public Health, 2012)
Background: in both Spain and Italy the number of immigrants has strongly increased in the last 20 years, currently representing more than the 10% of workforce in each country. The segregation of immigrants into unskilled or risky jobs brings negative consequences for their health. The objective of this study is to compare prevalence of work-related health problems between immigrants and native workers in Italy and Spain. Methods: data come from the Italian Labour Force Survey (n=65 779) and Spanish Working Conditions Survey (n=11 019), both conducted in 2007. We analyzed merged datasets to evaluate whether interviewees, both natives and migrants, judge their health being affected by their work conditions and, if so, which specific diseases. For migrants, we considered those coming from countries with a value of the Human Development Index lower than 0.85. Logistic regression models were used, including gender, age, and education as adjusting factors. Results: migrants reported skin diseases (Mantel-Haenszel pooled OR=1.49; 95%CI: 0.59-3.74) and musculoskeletal problems among those employed in agricultural sector (Mantel-Haenszel pooled OR=1.16; 95%CI: 0.69-1.96) more frequently than natives; country-specific analysis showed higher risks of musculoskeletal problems among migrants compared to the non-migrant population in Italy (OR=1.17; 95% CI: 0.48-1.59) and of respiratory problems in Spain (OR=2.02; 95%CI: 1.02-4.0). In both countries the risk of psychological stress was predominant among national workers. Conclusions: this collaborative study allows to strength the evidence concerning the health of migrant workers in Southern European countries.